Усадьба ожившего мрака - Корсакова Татьяна Владимировна (Королева мистического романа, 2022)
Экземпляры: ЦБ (20220627) / Инвентарный номер: 55167 / Цена: 307.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 69 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44